The rise of 5G technologies and systems: A quantitative analysis of knowledge production - Mendonça, S.; Damásio, B.; Freitas, L. C. de; Oliveira, L.; Cichy, M.; Nicita, A. (Telecommunication Policy, 2022)
The advent of a new generation of wireless communications has punctuated the dawn of every decade in recent times. Upgrades to mobile electronic systems represent faster and more robust capabilities of data transfer but bring with it a wide set of complementary changes as they are underpinned by harmonised specific spectrum bands, fresh international technical standards, new network operation requirements, innovative cellular devices as well as new services and a broader array of potential commercial use applications. This paper presents a systematic outline of the development of 5G-related research until 2020 as revealed by over 10,000 science and technology publications. The exercise addresses the emergence, growth, and impact of this body of work and offers insights regarding disciplinary distribution, international performance, and historical dynamics. Findings reveal the progressive growth of the 5G research over the years after original contributions in 2010 and point to a “take-off” around 2014. A set of stylised facts regarding this technology since its infancy are of interest to engineers, regulators and innovation strategists and policy-makers.